2021
DOI: 10.1097/qai.0000000000002709
|View full text |Cite
|
Sign up to set email alerts
|

Lessons From Rapid Field Implementation of an HIV Population-Based Survey in Nigeria, 2018

Abstract: Background:The need for accurate HIV annual program planning data motivated the compressed timeline for the 2018 Nigerian HIV/ AIDS Indicator and Impact Survey (NAIIS). The survey team used stakeholder cooperation and responsive design, using survey process and paradata to refine survey implementation, to quickly collect high-quality data. We describe processes that led to generation of data for program and funding decisions, ensuring HIV services were funded in 2019.Setting: Nigeria is the most populous count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Statistically significant odds ratios are bolded. ART, antiretroviral therapy; HIVDR, HIV drug resistance; PI, protease inhibitor.aCombining self-report and ARV biomarker.bAssessed via Limiting Antigen-Avidity enzyme immunoassays [19].cOnly majority HIV subtypes G and CRF02_AG were compared in regression analyses.dDetection of efavirenz, lopinavir, atazanavir, and nevirapine in blood specimens at the time of sample collection [21].eSelf-reported.fART-related statistics were calculated among participants with serological evidence of antiretroviral drugs at the time of sample collection.gNon-nucleoside reverse transcriptase inhibitor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistically significant odds ratios are bolded. ART, antiretroviral therapy; HIVDR, HIV drug resistance; PI, protease inhibitor.aCombining self-report and ARV biomarker.bAssessed via Limiting Antigen-Avidity enzyme immunoassays [19].cOnly majority HIV subtypes G and CRF02_AG were compared in regression analyses.dDetection of efavirenz, lopinavir, atazanavir, and nevirapine in blood specimens at the time of sample collection [21].eSelf-reported.fART-related statistics were calculated among participants with serological evidence of antiretroviral drugs at the time of sample collection.gNon-nucleoside reverse transcriptase inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…Survey sampling and population NAIIS was a cross-sectional survey of households throughout Nigeria conducted in 2018. The methodology of NAIIS has been previously described in detail [2,19]. Briefly, NAIIS was designed to provide estimates of HIV prevalence, HIV incidence, viral load suppression, and related health indicators from a nationally representative sample of the Nigerian population.…”
Section: Methodsmentioning
confidence: 99%
“…The primary objective of NAIIS was to obtain nationally representative estimates of HIV prevalence, incidence, and viral load suppression [5]. The methodology of NAIIS has been described in detail elsewhere [5,15]. For this analysis, we selected adults (aged 15–64 years) who tested positive for HIV in NAIIS and had ARV analytes in their blood at the time of sampling.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the design reduced data collection costs through significantly fewer call attempts [76]. Another example comes from Nigeria, where a population-based HIV survey adopted a responsive survey design that used paradata to expedite the survey data collection and release [77]. The overall data collection duration was reduced by 1 week from the original plan and saved about $4.4 million in costs.…”
Section: Applying Responsive and Adaptive Sampling Designmentioning
confidence: 99%